LIFE SKILLS MELALUI USAHA GULA SAWIT DALAM MENINGKATKAN EKONOMI KELUARGA DI DESA MAREDAN BARAT KECAMATAN TUALANG KABUPATEN SIAK - Saprina, Eli; Natuna, Daeng Ayub; Widiastuti, Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The formulation of the problem in this study is "How is sugar business life skills in Maredan Barat Village, Tualang Subdistrict, Siak Regency?", According to the formulation of the problem. Related to the benefits of this research are (1) For researchers, it is expected as the first step in the application of all knowledge that has been obtained during sitting in the field of lectures, and increase knowledge and insight on matters relating to sugar business life skills (2) For the community, Expected motivate the surrounding community and add new knowledge about sprouting business life skills and improve the business skills themselves (3) For knowledge carriers, it is expected to be able to add and complement theories that discuss the life skills of sugar businesses in Maredan Barat Village, Tualang District, Siak Regency ( 4) As reference material for other researchers. This research is a kind of descriptive research using qualitative research, this study consists of one variable, namely with 4 indicators and 12 sub indicators, namely the first indicator of personal skills with subfocus on knowledge-seeking skills, awareness of self-potential, thinking skills. Social skills with a subfocus on communication and conversation skills. Academic conversation with subfocus formulating hypotheses and completing trials. Conversational skills with subfocused skills in self-confidence, full adjustment skills, and skills in groups and organizations. The informants of this study were 5 people consisting of 2 core informants, 2 control informants, and 1 observer informant. The subject of this research was palm nira tappers in Maredan Barat Village, Tualang District, Siak Regency. Data collection techniques in this study are documentation techniques, observation techniques, and interview techniques.Key Words: Life Skills, Palm Sugar Business